2012
DOI: 10.1136/bmj.e8308
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the fittest: retrospective cohort study of the longevity of Olympic medallists in the modern era

Abstract: Olympic medallists live longer than the general population, irrespective of country, medal, or sport. This study was not designed to explain this effect, but possible explanations include genetic factors, physical activity, healthy lifestyle, and the wealth and status that come with international sporting glory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 23 publications
8
52
1
1
Order By: Relevance
“…Olympic medalists in endurance events had a survival of advantage over medalists in power events (39).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%
“…Olympic medalists in endurance events had a survival of advantage over medalists in power events (39).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%
“…A study of over 15,000 former Olympic athletes from 9 different countries showed a longevity benefit of approximately 3 years when compared to the general population. 7 An even more impressive 6-year survival (75.5 vs 69.9 years) was observed in 2600 Finnish athletes who competed in elite competitions between 1920-1965 compared to army recruits. 8 Similar findings have been replicated in former Tour de France participants 9 , Italian track and field athletes 10 , major league baseball players 11 , and professional tennis players 12 .…”
Section: The Benefits Of Exercisementioning
confidence: 98%
“…Former endurance and mixed sports athletes have lower mortality than the general population,13 but previous studies report inconsistent results for power sports athletes 14. However, very intense patterns of exercise may increase risk for cardiovascular morbidity and mortality compared with light to moderate amounts of exercise 9 15…”
Section: Introductionmentioning
confidence: 99%